Immunotherapy: An Iron Oxide Nanocarrier Loaded with a Pt(IV) Prodrug and Immunostimulatory dsRNA for Combining Complementary Cancer Killing Effects (Adv. Healthcare Mater. 7/2015). Issue 7 (May 2015) - Hernández‐Gil, Javier; Cobaleda‐Siles, Macarena; Zabaleta, Aintzane; Salassa, Luca; Calvo, Javier; Mareque‐Rivas, Juan C.
<x xml:space="preserve">Abstract</x> Micelles filled with iron oxide nanoparticles (IONPs) with a size suitable for effective lymphatic delivery are loaded with a cisplatin Pt(IV) prodrug and a immunostimulatory dsRNA (poly (I:C)) to provide targeted chemoimmunotherapy. On page 1034, J. C. Mareque‐Rivas and colleagues show that, compared to the free drugs, the poly (I:C)‐Pt(IV)‐IONPs exhibit greatly enhanced cancer cell killing properties and ability to activate dendritic cells.